2013
DOI: 10.2225/vol16-issue5-fulltext-12
|View full text |Cite
|
Sign up to set email alerts
|

Production of heterologous cutinases by E. coli and improved enzyme formulation for application on plastic degradation

Abstract: Background: The hydrolytic action of cutinases has been applied to the degradation of plastics. Polyethylene terephthalate (PET) have long half-life which constitutes a major problem for their treatment as urban solid residues. The aim of this work was to characterize and to improve stable the enzyme to optimize the process of degradation using enzymatic hydrolysis of PET by recombinant cutinases. Results:The wild type form of cutinase from Fusarium solani pisi and its C-terminal fusion to cellulose binding do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
1
3
0
3
Order By: Relevance
“…Similar effects have also been shown by Talukder et al (42), who used PEG 400 to increase the activity and stability of a lipase from Chromobacterium viscosum in sodium bis(2-ethyl-L-hexyl)sulfosuccinate (AOT)-isooctane reverse micelles, with the half-life increasing from 38 days in simple reverse micelles to 60 days in reverse micelles. Stabilization of low-molecular-mass PEG in aqueous nonmicellar solutions was also seen by Gomes et al (43). Furthermore, our study showed that DEG has an effect similar to that of PEG on these cutinases.…”
Section: Discussionsupporting
confidence: 89%
“…Similar effects have also been shown by Talukder et al (42), who used PEG 400 to increase the activity and stability of a lipase from Chromobacterium viscosum in sodium bis(2-ethyl-L-hexyl)sulfosuccinate (AOT)-isooctane reverse micelles, with the half-life increasing from 38 days in simple reverse micelles to 60 days in reverse micelles. Stabilization of low-molecular-mass PEG in aqueous nonmicellar solutions was also seen by Gomes et al (43). Furthermore, our study showed that DEG has an effect similar to that of PEG on these cutinases.…”
Section: Discussionsupporting
confidence: 89%
“…De acuerdo a la revisión del estado del arte, no se encontró información disponible respecto a la producción de cutinasas e hidrofobinas a partir de papel filtro como sustrato. Los estudios identificados, producen estas proteínas a partir de material lignocelulósico con polímeros lipídicos de la pared celular para el caso de las cutinasas, y fuentes de carbono simples como glucosa, lactosa o lignocelulósicos como tabaco, para el caso de las hidrofobinas (Castro, Peña, & Farrés, 2010;Chaudhari & Singhal, 2015;Gomes et al, 2013;Mendez, 2015). Más allá de la posible identificación, sería necesario realizar pruebas de actividad enzimática para este tipo de proteínas con el fin de identificar presencia o ausencia de estas.…”
Section: Cuantificación E Identificación De Proteínas En Extractosunclassified
“…These enzymes have been successfully applied for the biodegradation of plastics, as well as for the delicate superficial hydrolysis of polymeric materials prior to their functionalization, as has been reported by Nikolaivits et al [15]. Gomes et al [67] characterized and improved the stability of the enzyme to optimize the degradation process by enzymatic hydrolysis of PET by recombinant cutinases. The objectives were met using the cutinase from Fusarium solani pisi and its C-terminal fusion with the cellulose-binding domain N1 of Cellulomonas fim, produced by genetically modified Escherichia coli.…”
Section: Plasticsmentioning
confidence: 98%